2017
DOI: 10.1182/bloodadvances.2017007302
|View full text |Cite
|
Sign up to set email alerts
|

Near-tetraploidy is associated with Richter transformation in chronic lymphocytic leukemia patients receiving ibrutinib

Abstract: Key Points• Pretreatment near-tetraploidy is associated with advanced Rai stage, deletion of 17p, and complex karyotype.• Pretreatment near-tetraploidy is an independent risk factor for ibrutinib discontinuation via Richter transformation.Ibrutinib is a highly effective targeted therapy for chronic lymphocytic leukemia (CLL).However, ibrutinib must be discontinued in a subset of patients due to progressive CLL or transformation to aggressive lymphoma (Richter transformation). Transformation occurs early in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 23 publications
2
30
0
1
Order By: Relevance
“…Furthermore, they showed that near-tetraploidy was associated with discontinuation of ibrutinib due to Richter transformation. 6 Interestingly, two of our CLL patients had a Richter syndrome at the time of diagnosis.…”
Section: E107mentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, they showed that near-tetraploidy was associated with discontinuation of ibrutinib due to Richter transformation. 6 Interestingly, two of our CLL patients had a Richter syndrome at the time of diagnosis.…”
Section: E107mentioning
confidence: 88%
“…Small series or case reports have described the presence of NT in B cell precursor acute lymphoblastic leukemia (BCP-ALL), 1 T cell lymphoma, 2 marginal zone lymphoma (MZL), 3 hairy cell leukemia, 4 MCL, 5 and CLL. 6 Pui et al described a striking morphological finding with the presence of clumped chromatin and grooved nuclei in the majority of near-triploid and near-tetraploid BCP-ALL. 1 In MCL, tetraploid clones are more frequently observed in blastoid (36%) and pleomorphic variants (80%).…”
Section: Automated Differential White Blood Cell Count and Cytologicamentioning
confidence: 99%
“…The most important molecular factor is likely the type of clonal relationship between CLL and transformed cells, with clonally-related cases having a much worse prognosis. 8 Unfortunately, this could not be determined in our patients due to the lack of archived CLL cells. Furthermore, the International Prognostic Score (IPS), originally developed for de novo HL, was found to stratify prognosis among Hodgkin-RT patients from the Mayo Clinic database.…”
Section: Hodgkin's Variant Of Richter's Transformation During Ibrutinmentioning
confidence: 92%
“…In the case of DLBCL, overexpression of the CD79B was also reported to be responsible for primary ibrutinib resistance; however, such a mechanism was not reported in CLL [83]. Secondary resistance to BTK inhibitors is far better characterized in CLL, where it can be manifested as a Richter transformation during the first year of therapy or as progressive CLL [62,78,[84][85][86]. It was shown that CLL cells under ibrutinib pressure are prone to clonal shifts as determined by whole-exome sequencing studies [87,88].…”
Section: Resistance Mechanisms and Clinical Implicationsmentioning
confidence: 99%